2016
DOI: 10.13189/wjcat.2016.040102
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing the Use and Adoption of Mobile Phone Money Services

Abstract: The Mobile phone banking idea was initially born out of the intention to reach the unbanked rural poor. However, there still existed mobile phone money service divide, highly skewed against the rural poor population. This paper was therefore seeking to explore challenges facing mobile phone money services. Qualitative research technique was used. Further, both primary and secondary data was used. The study was conducted in Homa Bay region in Kenya, using ethnography research design. The study established that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Despite being relatively new, the area of mobile money services has received a lot of attention from different scholars largely due to its disruptive nature in the world of finance especially in the developing world. At the very basic level, studies in this area have focused on the factors behind its success (GSMA, 2010;Chauhan, 2015;IMF, 2019;GSMA, 2020), opportunities embedded in the innovation (Aron, 2018;Maino, et al, 2019) as well as challenges/limitations (Otieno, et al, 2016;Farooq, 2020).…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Despite being relatively new, the area of mobile money services has received a lot of attention from different scholars largely due to its disruptive nature in the world of finance especially in the developing world. At the very basic level, studies in this area have focused on the factors behind its success (GSMA, 2010;Chauhan, 2015;IMF, 2019;GSMA, 2020), opportunities embedded in the innovation (Aron, 2018;Maino, et al, 2019) as well as challenges/limitations (Otieno, et al, 2016;Farooq, 2020).…”
Section: Empirical Literaturementioning
confidence: 99%
“…Beyond the drivers, ability to bring the unbanked into the mainstream financial system, encouraging the culture of saving, potential to improve the efficiency of the financial services industry as well as employment creation are among the opportunities the innovation offers (Aron, 2018;Maino, et al, 2019). Meanwhile, insufficient agents' liquidity when it comes to servicing clients with large withdrawal needs (Otieno, et al, 2016); fraudulent activities such as identity theft, SMS scams and SIM swaps (Farooq, 2020;INTERPOL, 2020)in addition to episodes of network failure that makes the money inaccessible (Kubuga & Konjaang, 2016) are the most cited challenges.…”
Section: Empirical Literaturementioning
confidence: 99%
“…There is a large body of literature on the factors that impede the growth of mobile money services. The following factors were identified from various empirical contexts: income [6,10,11], bank account ownership [9,11,13]; age [14,15], education [10,16], sex [10,15], employment status [10,17], ease of use [6,13], perceived risk and trust [18,19] and awareness of services and benefits [17,20]. The review on factors delaying growth of mobile money from other literatures indicated that this subject is broader than what meets the eye.…”
Section: Literature Reviewmentioning
confidence: 99%